(untitled) (Journal of Plant Disease Sciences, 2020)
Rice grain discoloration is the disease of major importance in rice leads to the yield loss in Kuttanad region of Kerala. The field studies were undertaken for the management of the disease at Rice Research Station, Moncompu during Rabi 2016-17, Kharif 2017, Rabi 2017-18, Rabi 2018-19 and Kharif 2019. Twelve different treatments of organic and inorganic management aspects were implemented in the experiment. Among the treatments, the soil test based NPK + foliar spray of NK (1 %) + Soluble boron(0.2%) at 65 days after planting showed lower incidence of grain discoloration and gave better yield (4595 kg/ha) followed by 100% recommended dose of NPK+ PGPR mix-1 @ 7.5 kg/ha(3 times soil split application at 10,30,45 days after planting)+ PGPR mix-2 (2% foliar at 45 days after planting) and soil test based NPK + Multinutrient formulation (1% foliar at40 days after planting). It was also on par with soil test based NPK + 0.1% sodium silicate spray at 40 days after planting and also PGPR mix-1 @ 7.5 kg/ha (3 times soil split application at 10, 30, 45 days after planting)+ Pseudomonas spray 2%(50 days after planting) applied plot. Highest yield (4595 kg/ha) was recorded by the soil test based NPK + foliar spray of NK (1 %) + Soluble boron (0.2%) followed by 100% recommended dose of NPK+ PGPR mix 1 +PGPR mix-2 (4269 kg/ha). The mean yield loss due to grain discoloration was 2.05-22.8% in the farmers practice plot of 100% NPK(90:45:45 kg/ha) along with one prophylactic fungicide application (Carbendazim 12% + Mancozeb 63% 75 WP @1.5 g/l) at panicle emergence stage when compared with above effective treatments.